Three-Dimensional Stability of Unsaturated Excavation Slopes Under Different Seepage Conditions: A Case Study - Wang, Long; Deng, Hu; Xu, Meijuan; Li, Zhihua; Nie, Yuanhang; Huang, Qiuxia; Tang, Wei (Frontiers in Earth Science, 2022)
Three-dimensional stability analysis of soil slopes remains a hot topic in the field of geotechnical engineering. Considering the fluid-solid coupling effect, this paper performs a number of numerical analyses on the stability of a 3D excavation slope located in Wuxi Taihu Tunnel, China. Three typical cases of the issued slope are investigated, i.e., the slope at initial state, with water-stop curtain, and with both water-stop curtain and concrete sprayed layer. The shear strength reduction method was adopted to determine the factor of safety (FOS) of the slope. The distributions of pore pressures and wetting lines, the horizontal and vertical displacements and the critical slip surface are presented. The results indicate that, the water-stop curtain can prevent the groundwater seepage effectively. The water-stop curtain and concrete sprayed layer are effective in restraining the slope deformation, altering the critical slip surface and improving the slope safety.